Ethnopharmacological evaluation of schistosomicidal and cercaricidal activities of some selected medicinal plants from Ghana - Anyan, W.K.; Acheampong, D.O.; Owusu-Adzorah, N.; Armah, F.A.; Aninagyei, E.; Asiamah, E.A.; Thomford, A.K. (Tropical Medicine and Health, 2020)
Background: The adulticidal and cercaricidal activities of five Ghanaian medicinal plants, namely, Phyllanthus amarus, Vernonia amygdalina, Azadirachta indica, Morinda lucida and Nauclea latifolia against S. mansoni were evaluated in this study. Six weeks old ICR mice (n = 25) were percutaneously infected with S. mansoni cercariae. Nine weeks later, infected mice (n = 5) were anaesthetised and perfused for adult S. mansoni. Cercariae were treated with different concentrations (1000, 500, 250, 125, 62.5, 31.25 μg/mL) of methanolic extracts of the experimenting plants in triplicates. Adult S. mansoni incopula were also treated with same concentrations of each extract or 20 μg/mL praziquantel. The cercariae and adult worms were observed at time intervals for 180 min and 120 h to assess mortality and viability respectively. Additionally, 9-week cercariae-infected mice (4 groups of 5 mice) were treated with either 500 mg/kg po A. indica or V. amygdalina, 400 mg/kg po praziquantel or distilled water for 14 days. The mice were euthanized after adult worms were recovered from them. The liver was processed and histologically examined for granuloma formations. Results: All the plants exhibited varying cercaricidal and adulticidal activities against S. mansoni in a time and concentration-dependent manner. A. indica (3 h IC50 = 27.62 μg/mL) and V. amygdalina (3 h IC50 = 35.84 μg/mL) exerted the highest cercaricidal activity. Worm recovery after treatment with V. amygdalina, A. indica and praziquantel in vivo was 48.8%, 85.1 % and 59.9 % respectively (p < 0.05). A. indica and V. amydalina-treated mice recorded lesser mean liver and spleen weights compared to untreated groups (p < 0.05). Conclusion: A. indica demonstrated the highest cercaricidal and alduticidal activities in vitro, whereas V. amygdalina exhibited the most potent aldulticidal activity in vivo. This study could provide baseline information which can be used to develop plant-based alternative commercial drugs against S. mansoni.
Research Article
Keywords: Cercariae; Schistosoma mansoni; Azadirachta indica; Vernonia amygdalina